Gendered reproductions of epistemic violence and embodied silence - Sarafian, Iliana (Gender and violence in Romani and Traveller lives, 2025)
This chapter examines the epistemic violence evident in the voiced narratives of medical professionals who conceive Roma women’s reproduction as dangerous to the nation state and undeserving of care. These voices clash with the embodied silence of Roma women as a response to long-standing stereotyping of Roma childbirth as the reproduction of non-citizens. The chapter draws on the anthropological understandings of reproduction as political, sociocultural, and epistemic, and argues that epistemic violence is entangled with other forms of violence. It traces the origins of epistemic violence to the various meanings and causes of silence, including those embodied through traumatic experiences of stigma. When stigma and racism are constant in the past and the present in everyday life, silence becomes a critical tactic and a way of life predicated on embodied knowledge acquired from the politics of the ordinary experiences of quotidian injustice and epistemic dismissal of ‘the other.’ The chapter concludes with a discussion on the role of the researcher in interpreting the tacit character of embodied silence.